EKSTRAKSI DAN UJI POTENSI ANTIOKSIDAN DARI SENYAWA POLIFENOL JANTUNG PISANG CAVENDIS (Cavendis varadishii) YANG DIFERMENTASI ASAL PT. NUSANTARA TROPICAL FARM (NTF) LAMPUNG - N. Kurniawati; F. Khasbullah; Priyadi Priyadi (Universitas Lambung Mangkurat, 2021)
Banana blossom is waste, especially in PT. Nutrition Tropical Farm (NTF) as the largest bananaexporter in Lampung. Cavendis banana blossom in PT. NTF cannot be consumed like some other particular banana blossoms. Cavendis banana blossom from the company has a bitter tastebecause it contains high polyphenol compounds. High polyphenol compounds in the banana blossom can be acquired through an extraction process that furthermore can be used as antioxidants. By utilizing the polyphenol compounds in the banana blossom, it is possible to utilize and optimize the use value and economic value of the waste or by products of banana plant cultivation. The purposes of this study are 1) Increasing the acquisition of polyphenol extracts in Cavendis banana blossom extract from PT. NTF, 2) antioxidant activity by polyphenol compounds extract of Cavendis banana blossom from PT. Nusantara Tropical Farm. The result shows that spontaneous fermentation of the banana blossom affects the lignocellulose component and the acquisition of bioactive compounds. The highest yield of bioactive components extracts produced from 3 th day incubation for total polyphenols (982 mg/100mg), anthocyanin (25.34 mg/100 mg) and the highest antioxidant activity of catechin (37.74%) produced form 3 th day incubation.